EXPRESSING THE NAMES OF FAMOUS PEOPLE THROUGH PERIPHRASIS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This study explores the use of periphrasis as a linguistic tool to express the names of famous people, analyzing its significance in literary texts, journalism, and everyday communication. Periphrasis involves substituting direct names with descriptive phrases or indirect references, which can convey nuanced meanings, highlight specific attributes, or express cultural associations linked to these individuals. By employing periphrasis, speakers and writers can emphasize the qualities, achievements, or symbolic representations of famous figures without directly naming them. This approach not only enriches the language but also demonstrates creativity and stylistic variation, especially in contexts where discretion, rhetorical emphasis, or stylistic elegance is desired. The research focuses on identifying the different functions of periphrasis and examining examples from both English and Uzbek sources, highlighting the cultural differences and similarities in how renowned personalities are referenced indirectly.